Corrosion resistant properties of concrete using various supplementary cementitious materials. (2021) - Arunachalam, Sivakumar; Anandakumar, S.; Ranjani, R.; Rohith Varma, A.; Rajkumar, G.
Abstract: In the current situation, the waste disposal problem of industrial by-products like fly ash, rice husk ash, micro silica, Ground granulated blast slag furnace etc., become a vulnerable environmental issue due to the pollution. The present experimental investigation is focused on the mechanical and corrosion resistance properties of M30 grade of concrete with and without supplementary cementitious materials as a partial replacement of cement. Here the Fly ash is replaced to cement by 30% and GGBS by 40%. The cement was also replaced with composite supplementary cementitious materials such as Fly ash and Ground Granulated Blast Slag Furnace (GGBS) by 30% and 40%. Similarly the above blended mix is also made by adding micro silica by 10% with 20% Fly ash and 40% of GGBS mix. Here the various trail mixes are performed to examine compressive strength (C.S), split tensile strength (STS), flexural strength (FS) and modulus of elasticity (MOE) for the varying water cement ratio and the mechanical properties is observed for the concrete at 7 days and 28 days of curing. The half cell potential meter is used to compute the reinforced concrete subjected to accelerated corrosion for the trail mix concrete. It was observed that the concrete with cement as 60% as Fly ash as 30% shows the better behaviour out of concrete with other trail mixes.